Streptomyces lonarensis sp nov., isolated from lonar lake, a meteorite salt water lake in India - Sharma, Trupti K.; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Shinde, Vidhya K.; Zhan, Jing; Li, Wen-Jun; Rele, Meenakshi V.; Dastager, Syed Gulam; Kumar, Lalitha Sunil (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2016)
A novel alkaliphilic actinomycete, strain NCL716(T), was isolated from a soil sample collected from the vicinity of Lonar Lake, an alkaline salt water meteorite lake in Buldhana district of Maharashtra State in India. The strain was characterised using a polyphasic taxonomic approach which confirmed that it belongs to the genus Streptomyces. Growth was observed over a pH range of 7-11 at 28 A degrees C. The cell wall was found to contain ll-diaminopimelic acid and traces of meso-diaminopimelic acid. The major fatty acid components were identified as iso-C-16:0 (46.8 %), C-17:1 (12.4 %), anteiso-C-15:0 (5.1 %) and anteiso-C-17:1 (4.8 %). The major polar lipids were identified as diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol and phosphatidylinositol. The major menaquinones were determined to be MK-9 (H-6) (70.3 %), MK-9 (H-4) (15.5 %) and MK-9 (H-8) (7.2 %). The G+C content of the DNA of the type strain was determined to be 71.4 mol %. The 16S rRNA gene sequence has been deposited in GenBank with accession number FJ919811. Although the 16S rRNA gene sequence analysis revealed that strain NCL716(T) shares > 99 % similarity with that of Streptomyces bohaiensis strain 11A07(T), DNA-DNA hybridization revealed only 33.2 +/- A 3.0 % relatedness between them. Moreover, these two strains can be readily distinguished by some distinct phenotypic characteristics. Hence, on the basis of phenotypic and genetic analyses, it is proposed that strain NCL716(T) represents a novel species of the genus Streptomyces, for which the name Streptomyces lonarensis sp. nov., is proposed. The type strain is NCL 716(T) (=DSM 42084(T) = MTCC 11708(T) = KCTC 39684(T)).
Keywords: Alkaliphile; DDH analysis; Polyphasic taxonomy; Streptomyces lonarensis sp nov.